2019
DOI: 10.3390/polym11081248
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Polyamide (PA)12 Nanocomposites with Montmorillonite (MMT) Filler Clay Used for the Incremental Forming of Sheets

Abstract: In this paper, the preparation and characterisation of polymer materials suitable for single point incremental forming (SPIF) technology were performed. Three different kinds of mixtures were selected: a mixture of neat polyamide 12 (PA12), a nanocomposite with PA12 matrix and 1% clay (Cloisite 93A), and a nanocomposite with PA12 matrix and 3% clay (Cloisite 93A). Materials were produced using a melt intercalation method followed by compression moulding. According to the needs of SPIF technology, morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 77 publications
(83 reference statements)
1
19
0
1
Order By: Relevance
“…Further, the CNTs proportion inversely affects the voids density. Boric et al [ 24 ] introduced the idea of plasticization of polymers by adding foreign particles. They added clay Cloisite 93A in the polyamide and concluded that its addition from 1% to 3% increases the elongation from 44% to 49%, which in turn enhances the ISF formability.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the CNTs proportion inversely affects the voids density. Boric et al [ 24 ] introduced the idea of plasticization of polymers by adding foreign particles. They added clay Cloisite 93A in the polyamide and concluded that its addition from 1% to 3% increases the elongation from 44% to 49%, which in turn enhances the ISF formability.…”
Section: Introductionmentioning
confidence: 99%
“…Since the wear mechanism for polymers is mainly adhesive, and the wear is caused by frictional heat between the two contact surfaces, PA46 is capable of reducing damage thanks to the higher melting temperature and a less adhesive wear, due to a lower plastic deformation and a lower increase in contact area. On the other hand, both matrices, PA46 and PA12, have a higher crystallinity, near 70%, which keeps Young’s modulus very high (3300 MPa for P46 [ 53 ] and 1700 MPa for PA12 [ 54 ]), even up to temperatures near their melting point, avoiding higher levels of plastic deformation [ 64 ] and thus reducing the wear. In the case of the PA66 matrix, a more severe wear is achieved corresponding to the generation of higher temperatures on the sample surfaces due to the increased frictional heating.…”
Section: Resultsmentioning
confidence: 99%
“…As the early researches about ISF technology are mainly focused on metallic materials, there is an increased interest of transferring the research focus from metallic materials in ISF to thermoplastics, polymer foams [44], bilayer polymeric sheets [45,46] and also polymer-based composite materials, which are considered a kind of hard-to-form material [47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%